SITUATING CHARACTER BASED LEARNING OF ANTI-CORRUPTION THROUGH DIGITAL COMICS IN TEACHING ENGLISH - YULI ASTUTI HASANAH (JETLi: Journal of English Teaching and Linguistics, 2021)
The study described how the character based-learning of anti-corruption was situated in the English classroom by utilizing and creating digital comics in the Indonesian EFL context. The subjects of the study were the first semester students of State Islamic Institute of Kediri (IAIN Kediri). The research method used for this study was a descriptive qualitative research. It described the implementation of character based-learning of anti-corruption through digital comics which was explained in details from the beginning to the end of the study. Furthermore, the data were analyzed qualitatively. The data obtained from the results of recording on teaching learning process, the students’ participations, and the students’ scores on the project result of digital comics. It showed that the digital comics could raise the students’ enthusiasm to study English which could be shown from the result of observation during the teaching and learning process, the activeness of students’ participations in discussions and presentations, and the outstanding result of students’ creations on digital comics. The number of respondents in the research are 34 students. Based on the data on the category of content, grammar and choice of words, it showed that out of 34 students, 88% students performed excellently in organizing the story and delivering anti-corruption messages, while 12% of them performed good. Further, in terms of visualization, the researcher found that 32 students (94%) showed excellent visualization and arrangement of pictures or characters while 2 students (6%) performed good. At last, in presenting the comics, 71% of the students were excellent in fluency, mastery, and interactive performances, 8 students (23%) performed good, and the rest performed fairly good.